Projected Dietary Intake of Zinc, Copper, and Cerium from Consumption of Carrot (Daucus carota) Exposed to Metal Oxide Nanoparticles or Metal Ions - Ebbs, Stephen D.; Bradfield, Scott J.; Kumar, Pawan; White, Jason C.; Ma, Xingmao (Frontiers in Plant Science, 2016)
The expanding production and use of engineered nanomaterials have raised concerns about the potential risk of those materials to food safety and human health. In a prior study, the accumulation of Zn and Cu from ZnO, CuO, or CeO2, respectively, was examined in carrot (Daucus carota L.) grown in sand culture in comparison to accumulation from exposure to equivalent concentrations of ionic Zn2+, Cu2+, or Ce4+. The fresh weight concentration data for peeled and unpeeled carrots were used to project dietary intake of each metal by seven age-mass classes from child to adult based on consumption of a single serving of carrot. Dietary intake was compared to the oral reference dose (oral Rfd) for chronic toxicity for Zn or Cu and estimated mean and median oral RfD values for Ce based on nine other rare earth elements. Reverse dietary intake calculations were also conducted to estimate the number of servings of carrot, the mass of carrot consumed, or the tissue concentration of Zn or Cu that would cause the oral RfD to be exceeded upon consumption. The projections indicated for Zn and Cu, the oral RfD would be exceeded in only a few highly unrealistic scenarios of exceedingly high Zn or Cu concentrations in the substrate from ZnO or CuO or consumption of excessive amounts of unpeeled carrot. The implications associated with the presence of Ce in the carrot tissues depended upon whether the mean or median oral RfD value from the rare earth elements was used as a basis for comparison. The calculations further indicated that peeling carrots reduced the projected dietary intake by one to two orders of magnitude for both ENM- and ionic-treated carrots. Overall in terms of total metal concentration, the results suggested no specific impact of the ENM form on dietary intake. The effort here provided a conservative view of the potential dietary intake of these three metals that might result from consumption of carrots exposed to nanomaterials and how peeling mitigated that dietary intake. The results also demonstrate the utility of dietary intake projections for examining potential risks of nanomaterial exposure from agricultural foods.